EFEKTIVITAS KEBIJAKAN KRIMINAL DALAM PENANGGULANGAN TINDAK PIDANA NARKOTIKA (Dalam Kerangka Pembaharuan Hukum Nasional) - Bambang Joyo Supeno (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
Construction law gave birth to a policy aimed at realizing the substantive criminal policy. Law No. 35 of 2009 on Narcotics is a substantive criminal policy, which is accompanied by a variety of national and international cooperation agreements, as well as the enforcement of criminal law as a policy does not make the reduction in the number of empirical narcotic crime statistics kriminal. Terbukti, in the Annual Report of the Supreme Court of the Republic Indonesia Year 2014 and 2015 in narcotic cases are the first in the qualification cassation cases. State criminal policy does not formulate substantive philosophical convictions, sentencing guidelines and the formulation of criminal sanctions principal alternative character, as well as the absence of a social kind of criminal sanctions. In the criminal policies empirical application of criminal sanctions are likely to be low and can not be used as a deterrent factor and shock therapy